2008
DOI: 10.1088/0957-4484/20/1/015304
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the magnetization reversal in exchange-biased Co/CoO elongated nanorings

Abstract: We report on the control of magnetization reversal in exchange-biased Co/CoO nanorings resulting from the competition between field-cooling-induced unidirectional anisotropy at the Co/CoO interface and shape anisotropy of the elongated Co nanorings. We observed that the magnetization reversal mechanisms and magnitudes of exchange bias fields are strongly dependent on the strength and orientation of the cooling field relative to the major axis of the nanorings. Our results demonstrate a convenient technique to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
(23 reference statements)
1
17
0
Order By: Relevance
“…When the nanorings are field cooled at varying angles with respect to the major axis, the energetically favorable direction set in the CoO layer along the major axis due to shape anisotropy, is altered due to competition with the unidirectional anisotropy induced by field cooling. Applying the external field along the major axis will try to reorient the spins in the Co layer at different angles from the field cooling direction, and thus result in an increase in the exchange energy of the system [10]. We have thus shown that by adjusting the field cooling angle, the competition between shape anisotropy and unidirectional anisotropy was exploited to engineer the easy axis of the nanorings away from the intrinsic major axis.…”
Section: Exchange Biased Co/coo Nanoringsmentioning
confidence: 97%
“…When the nanorings are field cooled at varying angles with respect to the major axis, the energetically favorable direction set in the CoO layer along the major axis due to shape anisotropy, is altered due to competition with the unidirectional anisotropy induced by field cooling. Applying the external field along the major axis will try to reorient the spins in the Co layer at different angles from the field cooling direction, and thus result in an increase in the exchange energy of the system [10]. We have thus shown that by adjusting the field cooling angle, the competition between shape anisotropy and unidirectional anisotropy was exploited to engineer the easy axis of the nanorings away from the intrinsic major axis.…”
Section: Exchange Biased Co/coo Nanoringsmentioning
confidence: 97%
“…Since the discovery of EB in Co/CoO particles over 50 years ago, 9 it has been found in a variety of different systems with FM/AFM interfaces, including core-shell nanoparticles, [10][11][12] thin film systems, 3,5,13,14 lithographed nanostructures, [15][16][17][18] and (more recently) in high aspect ratio core-shell nanotubes (NTs). 19 The latter have attracted much interest due to their potential applications in nanoelectronic devices, catalysis, high-density recording media, and drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…11 However, so far, reported work on EB rings is very limited. [12][13][14][15] Exchange bias induced asymmetric magnetization behavior along the bias direction has been observed in magnetic ring structures, 16 but the detailed mechanism of magnetic reversal is not well understood.…”
Section: Introductionmentioning
confidence: 99%